Prediksi Tinggi Muka Air Tanah Pada Lahan Gambut Di Kabupaten Musi Banyuasin Provinsi Sumatera Selatan - Dina Aulia Fitri; Sigit Sutikno; Rinaldi Rinaldi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
During 2018 there were quite severe fires in South Sumatra, one of which was Musi Banyuasin Regency. Approximately 38,000 hectares of land were burned due to the condition of the vast and dry peatlands making it difficult to extinguish during a fire. The peat layer will also be prone to fire if the groundwater level is deeper than 40 cm. Efforts to maintain a height of less than 40 cm are monitored by the groundwater level by direct measurement in the field. High monitoring by direct measurement is carried out using a Sensory data transmission Service Assiated by Midori Engineering (SESAME) tool that can record rainfall, temperature, and surface water data. The purpose of this study is to make a prediction model of water level on peatlands using a regression method and predict water level on peatlands within a certain period. The results showed that the regression analysis with a period of 1 month, 3 months, and 6 months to get the results of the prediction of groundwater level with a strong correlation coefficient value of 0.756; 0.773; and 0.742. Whereas in the regression analysis for 9 months, the prediction results of the groundwater level with a moderate correlation coefficient are 0.524.Key words: groundwater level, rainfall, regression analysis, peat